Heights and Weights of Preschool Children Visiting the MCH Clinic of the General Hospital (RSUPP), Medan - Leman Sembiring; Leonard Napitupulu; S.M. Manoeroeng (Indonesian Pediatric Society, 1978)
The average height and weight of 4.082 children visiting the General Hospital (RSUPP), Medan, throughout 1969-1974 were higher than that reported by Sukonto et al. (1939). However, the heights and weights of school children at 5 to 6 years as reported by Hartaman et al. (1973) were higher than our findings in this study. Compared with the U.S. growth charts the height of these children was very close to the 10th percentile, while the weight was between the 3rd and the 10th percentile of the Harvard standard. At birth the average weight was very close to the 50th percentile of the Harvard standard, at one year it was very close to (below) the 10th percentile, while at 2-5 years it was slightly above the 3rd percentile.